2016
DOI: 10.1111/cogs.12351
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Requirements for the Emergence of Learned Signaling

Abstract: The emergence of signaling systems has been observed in numerous experimental and real‐world contexts, but there is no consensus on which (if any) shared mechanisms underlie such phenomena. A number of explanatory mechanisms have been proposed within several disciplines, all of which have been instantiated as credible working models. However, they are usually framed as being mutually incompatible. Using an exemplar‐based framework, we replicate these models in a minimal configuration which allows us to directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…(Millikan, 1998: 175) Aligning on shared communicative conventions draws upon two general resources. The first of these is feedback (De Ruiter et al, 2010; for overview, see: Spike et al, 2016): interlocutors are able to provide information to one another as to whether or not their interpretation is correct, allowing one, or both, of the parties to modify their behaviour in future interactions 6 . With feedback, speakers can modify their behaviour through trying to clarify the intended meaning, and use utterances which pick out relatively smaller sections of the context (Frank & Goodman, 2014: 85).…”
Section: Coordination Pressure: Communication and Conventionmentioning
confidence: 99%
“…(Millikan, 1998: 175) Aligning on shared communicative conventions draws upon two general resources. The first of these is feedback (De Ruiter et al, 2010; for overview, see: Spike et al, 2016): interlocutors are able to provide information to one another as to whether or not their interpretation is correct, allowing one, or both, of the parties to modify their behaviour in future interactions 6 . With feedback, speakers can modify their behaviour through trying to clarify the intended meaning, and use utterances which pick out relatively smaller sections of the context (Frank & Goodman, 2014: 85).…”
Section: Coordination Pressure: Communication and Conventionmentioning
confidence: 99%
“…Colaiori et al (2015;see also, Cuskley et al, 2017) used a model of three-state dynamics wherein agents have either a regular, irregular, or mixed (optionally regular or irregular) rule for a given lemma. This approach examined both gradual population turnover with biased child learners and memory limitations (also known as, information loss; Spike, Stadler, Kirby, & Smith, 2016). These factors, combined with a skewed frequency distribution of lemmas, recovered patterns in regularity reminiscent of natural language data (Carrol, Svare, & Salmons, 2012;Cuskley et al, 2014;Lieberman, Michel, Jackson, Tang, & Nowak, 2007), wherein highly frequent forms are more likely to be irregular given certain starting conditions.…”
Section: Earlier Modelsmentioning
confidence: 99%
“…For each lemma-inflection pairing, the agent stores: 1 f i , the total number of interactions with that inflection and lemma; 2 w, a weight for the lemma-inflection pair defined as the number of successful interactions with the lemma-inflection pair divided by the total number of interactions with the lemma-inflection pair, f i ; 3 t last , the time step of the last interaction with that lemma-inflection combination Agents have temporally constrained memory for each lemma-inflection combination. Memory limitations are crucial to recovering realistic frequency-dependent rule dynamics found in natural language (e.g., in corpora; Cuskley et al, 2017) and have been identified as an essential factor in the emergence of learned signaling in agent-based models more generally (Spike et al, 2016). This memory constraint is implemented as a deterministic loss of a lemma-inflection pairing after a set period of time: If a pairing has not been encountered within a specific time window, d = 100 (regardless of the pairing's weight, w), the pairing will be forgotten.…”
Section: Agent Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…We set out to answer the question by considering a particular situation in which communication is only available in task planning phase. In this case, the Our language generation problem has a connection with the work on the origin and evolution of natural languages, which has been studied earlier in evolutionary and computational linguistics [29,30]. Most of the prior works studied language evolution in the context of evolutionary games [31], for example, the talking heads experiment [32].…”
Section: Introductionmentioning
confidence: 99%